1994
DOI: 10.1073/pnas.91.15.6875
|View full text |Cite
|
Sign up to set email alerts
|

Participation of cyclin A in Myc-induced apoptosis.

Abstract: The involvement of c-Myc in cellular proliferation or apoptosis has been linked to differential cyclin gene expression. We observed that in both proliferating cells and cells undergoing apoptosis, cyclin A (but not B. C, D1, and E) mRNA level was elevated in unsynchronized Myc-overexpressing cells when compared with parental Ratla fibroblasts. We further demonstrated that Zn2+-inducible cyclin A expression was sufficient to cause apoptosis When Myc-induced apoptosis was blocked by coexpression ofBc1-2, the lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
144
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(154 citation statements)
references
References 26 publications
10
144
0
Order By: Relevance
“…These observations are in agreement with results from other authors, who demonstrated that a deregulation of c-myc is associated to an increase of cyclin E expression (Jansen-Durr et al, 1993;Daksis et al, 1994;Hanson et al, 1994;Hoang et al, 1994). However, even though evidences have been provided that c-myc is able to directly transactivate the expression of cyclin E, the mechanism involved remains unclear (Leone et al, 1997;PerezRoger et al, 1997).…”
Section: Discussionsupporting
confidence: 82%
“…These observations are in agreement with results from other authors, who demonstrated that a deregulation of c-myc is associated to an increase of cyclin E expression (Jansen-Durr et al, 1993;Daksis et al, 1994;Hanson et al, 1994;Hoang et al, 1994). However, even though evidences have been provided that c-myc is able to directly transactivate the expression of cyclin E, the mechanism involved remains unclear (Leone et al, 1997;PerezRoger et al, 1997).…”
Section: Discussionsupporting
confidence: 82%
“…Several genes that promote cell cycle transit have been suggested as c-Myc targets (Dang, 1999) and two of these, cyclin A and Cdc25A, have been suggested to participate in apoptosis by c-Myc (Hoang et al, 1994;Galaktionov et al, 1996). Integrins regulate cyclin A, which associates with CDK2 and promotes S phase progression.…”
Section: Myc Target Genes and Apoptosismentioning
confidence: 99%
“…Integrins regulate cyclin A, which associates with CDK2 and promotes S phase progression. Enforced expression of cyclin A in Rat1 cells is su cient to confer anchorage-independent growth capacity and susceptibility to apoptosis by serum deprival (Hoang et al, 1994). Cdc25A is a phosphatase responsible for activating cdc2.…”
Section: Myc Target Genes and Apoptosismentioning
confidence: 99%
“…In general, cultured young or c-myc -expressing fibroblasts, with greater proliferation rates, exhibit lesser resistance to apoptosis than senescent fibroblasts (Wang 1995;Evan et al 1992). This may be related to the need of cell cycle progres-sion for both proliferation and apoptosis (Hoang et al 1994;Wu and Levine 1994). In addition, the Bcl-2 protein, an inhibitor of apoptosis, is differentially expressed in young and senescent fibroblasts and is involved in their different susceptibility to apoptosis (Wang 1995).…”
mentioning
confidence: 99%